The requirement of the patient’s consent to the medical procedure - LALLOUCHE, Samira (Journal of Human Sciences, 2021)
Consent is the basic element of the contract, it is necessary not only for the formation of the medical contract but also for the performance of the contract. The doctor has an obligation not to perform any medical procedure without the patient’s prior consent. The validity of consent is based on the understanding of the information transmitted and the lack of consent is understood as the lack of respect for the person of the patient of his dignity and physical integrity. Thus, the dignity of the human being requires prior consent to any intervention. However, the need for patient consent sometimes becomes unnecessary.